2016
DOI: 10.1007/s13105-016-0499-z
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of regulator of calcineurin 1 in spinal cord injury

Abstract: Spinal cord injury (SCI) is a severe clinical problem worldwide. The pathogenesis of SCI is complicated and much is unknown. The current study was designed to investigate the possible role of regulator of calcineurin 1 (RCAN1) in SCI and to explore the possible molecular mechanisms. Rats were injected with LVshRNAi-RCAN1 and then contusion-induced SCI was established. We found that RCAN1 was significantly increased in spinal cord of rats with SCI. Knockdown of RCAN1 markedly facilitated the structural and func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…RCAN1 is also overexpressed in the brains of individuals with Down syndrome, a disorder with an increased prevalence of AD . Neuronal expression of RCAN1 also increases with aging, and in response to traumatic stressors such as spinal cord injury and exhaustive exercise in muscle . The nutrient stress hyperglycaemia also induces RCAN1 expression in myotubes and pancreatic β‐cells .…”
Section: Rcan1 Expressionmentioning
confidence: 99%
“…RCAN1 is also overexpressed in the brains of individuals with Down syndrome, a disorder with an increased prevalence of AD . Neuronal expression of RCAN1 also increases with aging, and in response to traumatic stressors such as spinal cord injury and exhaustive exercise in muscle . The nutrient stress hyperglycaemia also induces RCAN1 expression in myotubes and pancreatic β‐cells .…”
Section: Rcan1 Expressionmentioning
confidence: 99%
“…Our previous work revealed that such a negative effect can be a major contributing factor to the hyperexcitability of small-diameter DRG neurons that is a basis of neuropathic pain induced by SCI (Ritter et al, 2015a). A recent study reported RCAN1 upregulation in the spinal cord dorsal horn after SCI (Wang et al, 2016). However, it was not clear whether the reported upregulation occurred in spinal neurons or synaptic terminals from primary sensory inputs in the dorsal horn.…”
Section: Novel Role Of Ntid Phosphorylation Sites On the Modulation Omentioning
confidence: 93%
“…Although these studies link reduced CaN activity and persistent pain syndromes, the downstream ion channel targets responsible for the underlying hyperexcitability are not known. A recent study reported upregulation of the endogenous regulator of CaN 1 (RCAN1) in rat spinal cord after SCI (Wang et al, 2016). RCAN1 upregulation typically inhibits CaN, which might affect CaN-dependent modulation of ion channels in DRG neurons (Davies et al, 2007;Liu et al, 2009;Li et al, 2011;Patel et al, 2015).…”
Section: Significance Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…This prevented CST retraction and improved motor function. Local lentivirus‐mediated RNA interference (RNAi) of the regulator of calcineurin 1 suppressed the increase in IL‐1β and TNF‐α and improved behavioral performance in injured rats . Local transfection of siRNA against the TNF‐like weak inducer of apoptosis decreased IL‐1β and TNF‐α, and enhanced locomotor functional recovery in injured mice …”
Section: Local Delivery Of Therapeutic Agents Regulates Inflammatory mentioning
confidence: 99%